Photosynthesis of cassava and its relation to crop productivity - El-Sharkawy, Mabrouk A.; Mejía de Tafur, María Sara; Cadavid López, Luis Fernando (International Center for Tropical Agriculture, 1993)
Cassava (Manihot esculenta Crantz) is a hot-climate crop that is also grown in cool areas of the highland tropics, where yields are reduced. The purpose of this study was to evaluate the effect of growth temperature on photosynthesis of two cassava cultivars from contrasting habitat and to determine the relationship between yield and photosynthesis in a set of 15 field-grown cassava cultivars under rainfed conditions. Irrespective of the original habitat of cultivars, photosynthesis was substantially reduced in leaves developed in a cool climate as compared with warm-climate leaves. Cool-climate leaves partially recovered their photosynthetic capacity after 7 d acclimatization in a warm climate. The hot-climate cultivar showed a broad optimum temperature from 30 to 40\248C, while the cool-climate cultivar showed an upward shift in optimum temperature in the acclimatize and warm-climate leaves. In field-grown cassava, maximum net photosynthesis of upper canopy leaves was greater than 40 umol CO2 m(-2S-1) when measured in high rainfall season and the rates did not show light saturation up to 1800 umol m(-2S-1) PAR. The seasonal average net photosynthesis of upper canopy leave was significantly correlated with both root yield and harvestable biomass. It was concluded that selection for high photosynthesis in parental materials may lead to high yields when combined with other yield determinants.